MALAY LANGUAGE AND CULTURE IN THE PERSPECTIVE OF INDONESIAN: ANALYSIS OF LANGUAGE AND CULTURAL DYNAMICS - Yusari, Nur Indah; Soejono, Sri Rosmalina; Putriani, Ananda (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Malay language and culture have a very close relationship with Indonesian, considering the similarities in history, language structure, and cultural values. This study aims to analyze the dynamics of Malay language and culture from the perspective of Indonesian, as well as its implications for cultural identity and intercultural communication. Through qualitative analysis of literary texts, mass media, and social interactions, this study finds that Indonesian has been greatly influenced by Malay language and culture, especially in terms of vocabulary and sentence structure. However, there are also cultural dynamics that influence the use of language and cultural identity in both countries. This study contributes to a better understanding of the linguistic and cultural relations between Malay and Indonesian, as well as its implications for intercultural communication and cooperation in the Southeast Asian region.